2015
DOI: 10.1038/ni.3257
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor ATF7 mediates lipopolysaccharide-induced epigenetic changes in macrophages involved in innate immunological memory

Abstract: Immunological memory is thought to be mediated exclusively by lymphocytes. However, enhanced innate immune responses caused by a previous infection increase protection against reinfection, which suggests the presence of innate immunological memory. Here we identified an important role for the stress-response transcription factor ATF7 in innate immunological memory. ATF7 suppressed a group of genes encoding factors involved in innate immunity in macrophages by recruiting the histone H3K9 dimethyltransferase G9a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(167 citation statements)
references
References 60 publications
8
158
0
1
Order By: Relevance
“…Multiple proinflammatory genes were upregulated at the later time point, and this upregulation was accompanied by reduced amounts of epigenetic marks associated with gene silencing and the incomplete recruitment of ATF7, which was associated with the formation of heterochromatin. This study also found that treatment with ␤-glucan induced the phosphorylation of ATF7, a finding analogous to that observed after treatment with LPS (25). Similarly, our study showed the induction of tolerance, most notably, with ␤-glucan and BCG, when cells were only briefly left to rest before rechallenge (24 h), whereas a training effect was seen if cells were left to rest for 3 or 6 days.…”
Section: Figsupporting
confidence: 65%
“…Multiple proinflammatory genes were upregulated at the later time point, and this upregulation was accompanied by reduced amounts of epigenetic marks associated with gene silencing and the incomplete recruitment of ATF7, which was associated with the formation of heterochromatin. This study also found that treatment with ␤-glucan induced the phosphorylation of ATF7, a finding analogous to that observed after treatment with LPS (25). Similarly, our study showed the induction of tolerance, most notably, with ␤-glucan and BCG, when cells were only briefly left to rest before rechallenge (24 h), whereas a training effect was seen if cells were left to rest for 3 or 6 days.…”
Section: Figsupporting
confidence: 65%
“…We propose that, in our model, removal of repressive histone marks is more critical for long-term memory than the addition of active histone marks. In line with our observation, a recent paper studying long-term memory in primary macrophages concluded that removal of repressive H3K9 methylation enabled transcriptional memory induced by LPS exposure (35). In future studies, it will be interesting to survey the nucleosome landscape to query whether nucleosome depletion occurring during Pol II elongation is another event that is inherited, as suggested in recent studies of transcriptional memory in mammalian cells (6,7).…”
Section: Discussionsupporting
confidence: 54%
“…Additional studies have shown that the interplay between metabolic pathways, such as glycolysis and glutamine metabolism, is crucial for the induction of the epigenetic and functional changes that take place in monocytes during the induction of trained immunity 61,62 . Furthermore, a recent study showed that both LPS and β-glucan induce trained immunity through a mitogen-activated protein kinasedependent pathway that phosphorylates activating transcription factor 7 (ATF7), subsequently reducing levels of the repressive histone mark 63 . These data suggest that trained immunity is epigenetically and functionally the opposite process to the immune tolerance that is observed in sepsis; this hypothesis has been supported by recent genome-wide assessment of the histone modification landscape induced by either β-glucan (trained immunity) or LPS (immune tolerance) 60 .…”
Section: Reversal Of Immune Suppression In Sepsismentioning
confidence: 99%